The Financing Strategy of BMT An’fa NU as Supporting Member’s Business in Pucang Village - Fitriani, Wulan; Fitriyani, Yeny; Pudail, Muhammad (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
This study explores the role of Sharia Financing in BMT Anfa' NU Pucang, emphasizing its alignment with Islamic principles. It focuses on financing product types, operational methods, and strategies employed by BMT, specifically utilizing mudharabah and murabahah contracts. Interview results with BMT management underscore the organization's foundation, legal structure, and financial strategies. The research methodology employs a qualitative approach, literature review, and interviews, with data analysis utilizing thematic coding. BMT Anfa' NU provides inclusive financial access, supports micro-economic sustainability, and facilitates community empowerment. Innovations such as transparent profit-sharing offerings, no administration fees, and zakat tax deductions demonstrate BMT Anfa' NU's commitment to creating fair and sustainable financial solutions. The result is expected to bring more knowledge and another perspective on the financing strategy that can be applicable or can be developed in the next research. The limitation of this research is that it just takes one BMT for the subject of research.